2,5-Bis{[(−)-(S)-1-(4-bromophenyl)ethyl]iminomethyl}thiophene - Mendoza, Ángel; Bernès, Sylvain; Hernández Téllez, Guadalupe; Portillo Moreno, Oscar; Gutiérrez, René (Wiley-Blackwell, 2014)
The title compound, C22H20Br2N2S, was synthesized under solvent-free conditions. The molecule shows crystallographic C2 symmetry, with the S atom of the central thiophene ring lying on a twofold rotation axis. Furthermore, as a consequence of the (S,S) stereochemistry, the molecule has a twisted conformation. The dihedral angle between the thiophene and benzene rings is 72.7 (2)° and that between the two benzene rings is 55.9 (2)°. In the crystal, molecules are arranged in a chevron-like pattern, without any significant intermolecular interactions.